Subacute knee pain and swelling in a healthy male: a case of Brodie's abscess. Issue 3 (20th March 2019) - Patel, Mitesh K; Barrientos, Steven; Gupta, Sunny; Tucker, Bradford
Abstract : Osteomyelitis is an inflammatory process of the bone caused by an infection. The key to successful management is early recognition and treatment, as complications can arise if interventions are not done in a timely manner. Subacute or chronic osteomyelitis is associated with avascular necrosis of bone requiring surgical debridement and antibiotic therapy. Here, we describe a case illustrating an uncharacteristic presentation of knee pain ending with multiple surgical debridements in a healthy male.